The Devonian Discinids of the Northwest Edge of the Paraná Basin (Ponta Grossa Formation, Mato Grosso do Sul), Brazil - Mariana Batista da Silva; Jeanninny Carla Comniskey; Sandro Marcelo Scheffler (Terr@ Plural, 2021)
In Brazil, discinid brachiopods are found abundantly in the Devonian strata of the Paraná Basin, on the northwest and east edges. This work aims to describe species of discinids from the state of Mato Grosso do Sul, Brazil, at the northwest edge, that is lesser studied. Five taxa of discinids were recognized: Orbiculoidea baini, Orbiculoidea bodenbenderi, Orbiculoidea excentrica, Gigadiscina collis, and Rugadiscina sp. This paper expands the knowledge of the distribution of the discinids in the Devonian of Brazil, showing its high representativeness in Mato Grosso do Sul, especially during the Pragian-early Emsian.